Applying Six Sigma (SS) to Improve the Quality of Academic Life (QAL) - Abbas Bahia, Taher Hameed; Afrah Raheem Idan, Hinwa Hussein Ahmed, (Opción, 2019)
The current study looks forward to the possible application of Six Sigma as an input to improve the quality of academic life using a set of statistical methods through the SPSS vr.24 software. As a result, an increase in the value of (SS) by one unit leads to an increase in the value of (QAL) by (0.65). In conclusion, the paper shows that the lack of improvement towards the satisfaction of staff and students and the quality of its outputs and limited adoption of information technology will lead to creativity and innovation in the field of work.